Studies on the formation and stability of nano-crystalline Al50Cu28Fe22 alloy synthesized through high-energy ball milling - Yadav T.P.; Mukhopadhyay N.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
This work reports the formation of nano-crystalline Al50 Cu28Fe22 alloy by high-energy ball milling. The Al50Cu28Fe22 alloy, synthesized through slow cooling of the molten alloy, was subjected to milling in an attritor mill at 400 rpm for 5 h, 10 h, 20 h, 40 h and 80 h with a ball to powder ratio of 40:1 in hexane medium. The X-ray diffraction and transmission electron microscopy observation of milled samples revealed that the milling duration of 5-40 h has led to the formation of nano-phase. The average crystallite size has been found to be of ∼17 nm. When the nano-crystalline alloy was vacuum annealed at a temperature of ∼500 °C for 5-20 h, new structural phases corresponding to the superstructures of crystallite size around 100-200 nm of the parent nano-crystalline phase were identified. The superstructures have been found to correspond to the simple cubic structure with asc = √2ap and the face centred cubic structure with afcc = 2ap (ap: lattice parameter of parent nano-crystalline alloy). It has been proposed that the formation of two different types of superstructures resulting from ball milling followed by annealing is possibly governed by the minimization of free energy of phase constituents. © 2004 Elsevier B.V. All rights reserved.